Prospects for partnership : industrialization and trade policies in the 1970s - Hughes, Helen; World Bank. (Baltimore ; London : Johns Hopkins University Press, 1973)
This volume consists of papers, and comments, from a seminar on prospects for partnership between developed and developing countries, held by the World Bank in 1972.
"A seminar held at the International Bank for Reconstruction and Development, October 5 and 6, 1972."
Includes bibliographical references.
lje 19/02/2018
Loans
Keywords: Commercial policy; Industrialization; Commerce